Prácticas innovadoras en la formación del docente universitário - Lucarelli, Elisa (Educação)
This article discuss the problem of pedagogical preparation of university teachers in relation with the development of innovative practices at this level. Looks at the Latin America university in the context of inequity and poverty, large budgetary cuts and high expectations regarding educational quality at the higher education level. Presents experiences of university teacher education in Spanish and Argentine universities with characteristics of an alternative way to prepare teachers in its organization and implementation